Fundamentals of pediatric orthopedics - Staheli, Lynn T. (Lippincott Williams & Wilkins, 2016)
Ideal for anyone involved in the care of children with musculoskeletal problems, this best-selling resource has been completely updated to be even more relevant to your everyday practice. Comprehensive and user-friendly, it covers the diagnosis and management of pediatric orthopedic issues with an emphasis on the welfare of the whole child.